CircSNHG5 Sponges Mir-495-3p and Modulates CITED2 to Protect Cartilage Endplate From Degradation - Zhang, Jian; Hu, Shen; Ding, Rui; Yuan, Jinghong; Jia, Jingyu; Wu, Tianlong; Cheng, Xigao (Frontiers in Cell and Developmental Biology, 2021)
Background Intervertebral disc degeneration (IDD) is a highly prevalent degenerating disease that produces tremendous amount of low back and neck pain. The cartilage endplate (CEP) is vitally important to intervertebral discs in both physiological and pathological conditions. In addition, circular RNAs (circRNAs) have been shown to be involved in the regulation of various diseases, including IDD. However, the particular role of circRNAs in cervical vertebral CEP degeneration remains unclear. Here, we examined the unique role of circRNAs in CEP of patients with cervical fracture and degenerative cervical myelopathy (DCM). Methods Human competitive endogenous RNA (ceRNA) microarray was performed by previous research. Western blot (WB), immunofluorescence (IF), quantitative RT-PCR (qRT-PCR), luciferase assay, and fluorescence in situ hybridization (FISH) were employed to analyze the function of circSNHG5 and its downstream effectors, miR-495-3p, and CITED2. Results We demonstrated that circSNHG5 expression was substantially low in degenerative CEP tissues. Knockdown of circSNHG5 in chondrocytes resulted in a loss of cell proliferation and followed by degradation of extracellular matrix (ECM). In addition, circSNHG5 was shown to sponge miR-495-3p and modulate the expression of the downstream gene CITED2. This mechanism of action was further validated via overexpression and knockdown of CITED2. Conclusion Our findings identified a novel circSNHG5-miR-495-3p axis responsible for IDD progression. Future investigations into IDD therapy may benefit from targeting this axis.